The Marine Environment of Arab Scientists Mediterranean (Sea of Rome) as a Model - Abdul Karim Abdul Razzaq, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
There is a close link between human beings, the environment, and sustainability. This depends on the cultural paths that have emerged and are still showing their environmental impact. It highlights trends that are largely associated with climate change, where the environmental features of the Mediterranean (historical) are sought to reassure humans to survive. And the evolution of the environment. For mankind during the historical and geological phases passed by the study area, the stages of the phases decrease the level and area of the medieval sea (the Sea of Rum). It has undergone complex climate changes that have been accurately described by Arab scientists. This has created an increase in cultural and historical sites, and this is evident from the social diversity coinciding with climate change and the human environment. This has generated a special culture of archaeological sites that clearly surround the areas of the study area.